Limites e possibilidades da educação física nas políticas públicas de saúde de Vitória-ES - Bachetti, Jayanna de Rezende (2014)
The objective of this research is to investigate the limits and possibilities of the inserts of Physical Education in the planning of public health policies in Vitória - ES as a joint action to promote public health. We sought to ascertain which the existing initiatives proposed by the Municipal Health Department (MHD) were, and what the prospects for intersectoral proposed actions with other sectors of public administration using corporal practices in health. This is a documentary research with a qualitative approach. In the initial stage, we conducted a literature survey in order to gather information aimed at the elaboration of a theoretical support on the issue of research. We also made a survey of the laws and decrees that are in effect and that rule the health system of our country. In the second stage, we conducted a document collection on the MHD website, as well as at the department itself, of the documents considered relevant and dealing with the period between the years 2005 and 2012. For the data analysis, the technique used was the content analysis, which provides for a cut of the texts according to the most meaningful content for the following clustering and categorization of the answer units. It was verified that the speech found in the documents is one of a broader view of health, but in the analysis of the proposed actions, we realized that physical activity is still guided by the kind that primarily acts on the biological health of the individual. It was also found that even initially, the city of Vitória has entered Physical Education professionals within multidisciplinary teams, thus enhancing health actions proposed by the county. In that regard, to the joint actions' approach to health promotion, the intersectoriality and social participation were evident, but in the simplistic way. Such intersectoriality, most often occurs horizontally. Regarding social participation, we found that although there are mechanisms that facilitate this participation in health management, for a lack of data, we can not claim that they are effective in practice.